The Influence of Culture on the Negotiation process – Differences and similarities in conducting negotiation in France and Poland - Baranowski, Nicolas (My University, 2016)
The main objective of this thesis is to analyze both French and Polish negotiation styles and to determine in what extend a specific culture influences the negotiation process. The analysis of the French and Polish negotiation styles was studied through interviews of French and Polish negotiators with various negotiation experience. Moreover, the aim is to examine the negotiation process and to highlights the similarities and the differences between France and Poland in negotiation. The theoretical part explores the existing literature regarding the influence of culture on negotiation and also regarding the negotiation process. This is why theories developed by Hofstede, Lewis or Gauri are mentioned. Several models of negotiation are also explained. For the qualitative part, negotiators with a knowledge whether of both Polish and French cultures or just of one of them were selected. Following a case study research strategy, the findings from five semi-structured interviews reveal that a particular culture has an important influence on the negotiation process. The findings also revealed that the main differences between Poles and French in business negotiation lay in three categories: communication, the negotiation process, and the relationship between negotiators. However, those differences seem to be less important than the similarities. Indeed, France and Poland have two cultures that are similar in many ways and the result is that the main characteristics of negotiation remain similar. For instance, the approach to time, the process of the negotiation and the general framework for negotiation are quiet similar for both countries.
Keywords: Negotiation; Culture; France; Poland; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|